2017
DOI: 10.4172/2329-9096.1000395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Length of Bed Rest during Hospitalization on Skeletal Muscle in Patients with Conservatively Treated Acute Aortic Dissection

Abstract: Background: Little evidence exists on the effects of exercise guidance in patients with acute aortic dissection after a period of complete bed rest. Few studies have examined changes in skeletal muscle during such periods in patients with cardiovascular disease. This retrospective study sought to investigate changes in skeletal muscle in the standard rehabilitation period in patients with aortic dissection and to discuss an optimal rehabilitation approach to promote safe early return to the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Muscle atrophic processes begin within 72 h and muscle strength is reduced by 10-30% after 1 week of bed rest. 35 Takahashi et al reported that muscle strength is rapidly lost during hospitalization for cardiovascular disease, 36 and Fan et al noted that patients with documented ICUAW had worse physical functioning and health-related quality of life. 37 Clearly, ICUAW affects long-term physical function and ADL after cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle atrophic processes begin within 72 h and muscle strength is reduced by 10-30% after 1 week of bed rest. 35 Takahashi et al reported that muscle strength is rapidly lost during hospitalization for cardiovascular disease, 36 and Fan et al noted that patients with documented ICUAW had worse physical functioning and health-related quality of life. 37 Clearly, ICUAW affects long-term physical function and ADL after cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%